Respuesta :
Answer:
10.5
Step-by-step explanation:
Substitute 27 instead of y into the equation:
[tex]3x-\dfrac{1}{2}\cdot 27=18.[/tex]
Then
[tex]3x-13.5=18,\\ \\3x=18+13.5,\\ \\3x=31.5,\\ \\x=\dfrac{31.5}{3}=10.5.[/tex]
For this case we have the following equation:
[tex]3x- \frac {1} {2} y = 18[/tex]
We want to know the value of the variable x when [tex]y = 27[/tex]
For this, we substitute:
[tex]3x- \frac {1} {2} 27 = 18\\3x = 18 + \frac {27} {2}\\3x = \frac {36 + 27} {2}\\3x = \frac {63} {2}\\x = \frac {63} {6}\\x = \frac {21} {2}[/tex]
Answer:
[tex]x = \frac {21} {2}\ when\ y = 27[/tex]